Cross-sectional space-time modeling using ARNN(p, n) processes - Kazuhiko Kakamu; Wolfgang Polasek (Institute for Advanced Studies (IHS), 2007)
We suggest a new class of cross-sectional space-time models based on local AR models and nearest neighbors using distances between observations. For the estimation we use a tightness prior for prediction of regional GDP forecasts. We extend the model to the model with exogenous variable model and hierarchical prior models. The approaches are demonstrated for a dynamic panel model for regional data in Central Europe. Finally, we find that an ARNN(1, 3) model with travel time data is best selected by marginal likelihood and there the spatial correlation is usually stronger than the time correlation.
Keywords: C11; C15; C21; R11; 330; dynamic panel data; hierarchical models; marginal likelihoods; nearest neighbors; tightness prio; spatial econometrics; Konjunkturprognose; Regionales Wachstum; Theorie; Schätzung; Mitteleuropa